Effectiveness of Pain, Disease Severity and Radiological Grading on Disability of Daily Living Activities in Knee Osteoarthritis - Saime Ay; Deniz Evcik (Archives of Rheumatology, 2008)
Objective: In this study we planned to investigate the effects of pain, disease severity, and radiological grading on the disability of daily living activities in knee osteoarthritis (OA) patients, and to find out the determinative factors. Patients and Methods: A total of 50 knee OA patients who were admitted to the outpatient clinic of Physical Medicine and Rehabilitation clinic were included this study. The diagnosis was based on the American College of Rheumatology (ACR) criteria. Patients were evaluated according to pain, disease severity, radiological grading, and disability in daily living activities parameters. Pain was assessed by using Visual Analogue Scale (VAS; 0-10cm), disesae severity was measured by Lequesne severity index, radiologic grading was based on Kellgren and Lawrence OA criteria and disability was assessed by using the Health assessment Questionnaire (HAQ). Results: The mean age of the patients was 52.88 (±10.60) years and the mean disease duration was 72.41 (±61.00) months. A statistically significant relation was found between disease severity and age (r=0.66), disease duration (r=0.76), pain (r=0.83) and radiological grading (r=0.53) (p<0.01). However no significant relationship was observed between radiological findings and disability (p>0.05). The most significant correlation was found between disability, the Lequesne disease severity index and pain (p<0.01, r=0.55; p<0.01, r=0.50). Conclusion: Pain and disease severity affect the level of disability in daily activities. Therefore in additional to radiological grading, asssesment of disability which is of major importance to patients should also be taken into consideration during the follow-up period of knee OA. (Rheumatism 2008; 23: 14-7)